The equality impact of the Covid-19 pandemic on the Irish labour market - Alamir, Anousheh; Frances, McGinnity; Russell, Helen (ESRI; Irish Human Rights and Equality Commission (IHREC), 2024)
The COVID-19 pandemic had a profound impact on the lives of people in Ireland and around the world. Yet while everyone was impacted, there is abundant evidence the effects were not equally experienced across all members of society. Moreover, while there was much research on the immediate effects of the pandemic and the public health measures to address it, to date there is relatively little evidence on which effects have persisted once the immediate crisis had passed. Here we focus on one aspect of the pandemic – the labour market impacts – and consider the evidence of how structurally vulnerable groups – those particularly at risk of inequality or having their rights denied – have fared.1 The approach taken builds on previous research analysing equality at work in Ireland, by comparing the labour market situation of groups protected under Irish equality legislation for whom robust evidence is available (McGinnity et al., 2021). In this report the focus is the pandemic, therefore we compare the situation of these groups in terms of their employment and the nature of their jobs pre-pandemic in 2019 compared to 2022, using large, representative data sources with identical definitions of groups and labour market outcomes in both years. The key research question is: how has the labour market impact of COVID-19 in Ireland differed by gender, age, marital status, family status, educational qualifications, and disability status? The labour market is the major source of income for households, and exclusion from employment can have long-term effects on poverty risk, standard of living and inequality (McGinnity et al., 2021).